2020
DOI: 10.3390/md18020074
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of Marine Coral Microparticles into Collagen-Based Scaffolds Promotes Osteogenesis of Human Mesenchymal Stromal Cells via Calcium Ion Signalling

Abstract: Composite biomaterial scaffolds consisting of natural polymers and bioceramics may offer an alternative to autologous grafts for applications such as bone repair. Herein, we sought to investigate the possibility of incorporating marine coral microparticles into a collagen-based scaffold, a process which we hypothesised would enhance the mechanical properties of the scaffold as well its capacity to promote osteogenesis of human mesenchymal stromal cells. Cryomilling and sieving were utilised to achieve coral mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…In fact, the unique feature of this novel scaffold is its ability to restore the subchondral bone, as documented by extensive in vitro studies, which showed not only its osteoinductive and osteoconductive capabilities but also unique osteotransductive properties, that is, the formation of bone through the direct deposition of bone trabeculae on the scaffold material. 1,15,20,34,43 The chondrogenic potential of the articular phase of the scaffold has been studied in another ex vivo trial, 5 and these findings were also confirmed in a goat model in which the scaffold was able to restore the entire osteochondral unit even in extremely large defects. 26-28…”
mentioning
confidence: 87%
“…In fact, the unique feature of this novel scaffold is its ability to restore the subchondral bone, as documented by extensive in vitro studies, which showed not only its osteoinductive and osteoconductive capabilities but also unique osteotransductive properties, that is, the formation of bone through the direct deposition of bone trabeculae on the scaffold material. 1,15,20,34,43 The chondrogenic potential of the articular phase of the scaffold has been studied in another ex vivo trial, 5 and these findings were also confirmed in a goat model in which the scaffold was able to restore the entire osteochondral unit even in extremely large defects. 26-28…”
mentioning
confidence: 87%
“…They can proliferate and differentiate into osteoblasts upon appropriate stimuli. MSCs isolated from bone marrow are regarded as the gold standard [ 14 , 53 , 55 , 57 , 67 , 68 , 73 , 76 , 77 , 79 , 83 , 91 , 94 , 98 , 107 , 108 , 109 ]. MSC-like cells isolated from the stromal vascular fraction of the adipose tissue, namely, adipose-derived stem cells, ASC, are seldom used in selected applications [ 2 , 65 , 72 , 82 , 89 , 104 , 109 , 110 , 111 , 112 ].…”
Section: Biomaterials Osteoinductivity and Osteoconductivitymentioning
confidence: 99%
“…The analysis of alkaline phosphatase (ALPL) activity is one of the most common tests used to evaluate the osteogenic process and numerous easy-to-use and highly sensitive assays to measure ALPL activity are available on the market [ 14 , 53 , 54 , 55 , 58 , 61 , 65 , 66 , 67 , 68 , 70 , 71 , 73 , 76 , 79 , 80 , 83 , 85 , 86 , 88 , 90 , 91 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 107 , 114 , 115 ].…”
Section: Biomaterials Osteoinductivity and Osteoconductivitymentioning
confidence: 99%
“…As lower marine invertebrates, corals represent some of the most common animals in the ocean and can generally be categorized as soft, hard, or gorgonian. Coral extracts possess broad health benefits, including anti-inflammatory 55 antitumor, 56 tissue repair, 57 neuroprotective, 58 and anti-hypertensive effects. 59 All the compounds summarized in this section are purified marine coral-derived products.…”
Section: Coralsmentioning
confidence: 99%